2005
DOI: 10.1038/sj.cgt.7700887
|View full text |Cite
|
Sign up to set email alerts
|

The insulinoma-associated 1: a novel promoter for targeted cancer gene therapy for small-cell lung cancer

Abstract: The insulinoma-associated 1 (INSM1) gene is expressed exclusively during early embryonal development, but has been found reexpressed at high levels in neuroendocrine tumors. The regulatory region of the INSM1 gene is therefore a potential candidate for regulating expression of a therapeutic gene in transcriptionally targeted cancer gene therapy against neuroendocrine tumors. We analyzed expression of a reporter gene from a 1.7 kb region of the INSM1 promoter in a large number of small-cell lung cancer (SCLC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…An altered expression in some types of cancer has also been reported for INSM1. For example, it is reexpressed in neuroendocrine tumors (23) and its expression is increased in small cell lung cancer (24). However, no link between INSM1 expression and breast cancer tumors has been reported thus far.…”
Section: Discussionmentioning
confidence: 99%
“…An altered expression in some types of cancer has also been reported for INSM1. For example, it is reexpressed in neuroendocrine tumors (23) and its expression is increased in small cell lung cancer (24). However, no link between INSM1 expression and breast cancer tumors has been reported thus far.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, transient transfection of the INSM1 promoter-driven HSV-TK construct into the GLC-16 and H69 SCLC cell lines treated with increasing doses of ganciclovir showed an 80% kill rate in vitro. 21 We exploited the spatial and temporal regulatory features of the INSM1 promoter to develop an adenoviral delivered HSV-TK suicide gene therapy for the treatment of pediatric neuroendocrine tumors retinoblastoma, neuroblastoma and medulloblastoma. 22 In our studies, we demonstrated specific activation of the HSV-TK gene in Y79, IMR-32 and D283Med cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 Use of a nonviral INSM1 promoter-driven suicide gene therapy for SCLC has been demonstrated. 21 We developed an adenoviral INSM1 promoter-driven suicide gene therapy approach for the potential treatment of a variety of INSM1-positive pediatric neuroendocrine tumors. 22 In this study, in vivo imaging of the Ad-INSM1 promoter luciferase2-IRES-HSV-TK suicide gene therapy revealed off-target activity of the INSM1 promoter in mouse pancreas, kidney and lung.…”
Section: Introductionmentioning
confidence: 99%
“…12 Transient luciferase reporter gene transfection assay Cells (adherent cells plated 1 day prior to transfection) were transfected in duplicate with 0.5 mg plasmid DNA using Lipofectamine 2000 in OPTIMEM (Invitrogen) in 24-well dishes. For DMS53 and DMS456, 0.2 Â 10 6 cells per well were plated and for all other cell lines 0.1 Â 10 6 cells were plated per well.…”
Section: 7hash1-lucmentioning
confidence: 99%
“…Furthermore, the INSM1 promoter was capable of inducing high and SCLC-specific cytotoxicity in a suicide gene assay in vitro. 12 Another gene highly upregulated in SCLC encodes the basic helix-loop-helix transcription factor human achaetescute homolog 1 (alias hASH1, ASH1 and ASCL1 in humans and MASH1 in rodents). 13 Global gene expression profiling indicates expression levels of hASH1 to be 5-to 8-fold higher than INSM1 in SCLC suggesting the hASH1 promoter to be a strong regulatory candidate.…”
Section: Introductionmentioning
confidence: 99%